Expression of GAGE family proteins in malignant melanoma - Bazhin, Alexandr V.; Schnölzer, Martina; Schadendorf, Dirk; Eichmüller, Stefan B. (Cancer letters, 2007)
Cancer/testis antigens are considered as promising targets for immunotherapy against tumors including malignant melanoma. One group of these antigens is the GAGE antigen family. In this study, we obtained recombinant GAGE-7b protein against which a rabbit antiserum was generated. The polyclonal, monospecific antibodies were used to analyze the expression of GAGE family proteins in human melanoma tissues and cell lines. GAGE expression in melanoma cell lines ranged from 41% to 58% and in melanoma tissues from 22% to 53%. Immunohistochemical analysis of melanoma tumors revealed a rather heterogeneous expression of GAGE resulting in individual positive cells or foci of stained cells. Furthermore, we could show that autoantibodies against GAGE family proteins are detectable in 6% of melanoma patients. Besides, we first demonstrated that the expression of GAGE family proteins can be stimulated with 5′-aza-2′-deoxycytidine and trichostatin A. Through upregulation of protein expression GAGE family proteins might develop into promising targets for immunotherapy of melanoma and other tumors.